Investigation of Solar Energy: The Case Study in Malaysia, Indonesia, Colombia and Nigeria - Ho, Soon Min; Lomi, Abraham; Okoroigwe, Edmund C.; Urrego, Leonardo Rodriquez (IJRER, 2019)
In the present scenario of world (a growing world population & developing countries), the increasing consumption of electricity controls the progress of different forms of energy (renewable or nonrenewable energy) use around the world. Fossil fuels are non-renewable sources, and accounted for 81 % of total energy demand in 2017. However, there are some disadvantages associated with their use such as environmental pollution, emissions of greenhouse gasses, and they are depleting at a faster rate. Therefore, researchers have to work hard in order to find an alternative (such as solar energy) way for fossil fuel to generate energy. A large number of investigations on the solar energy have been carried out by many researchers in order to improve the living conditions, to help reduce air pollution and to go green. The purpose of work is to explore the current status, challenges, recent efforts and future prospects of solar energy in different countries including Malaysia, Indonesia (Asia region), Nigeria (Africa region) and Colombia (South America).